THE PROGRESSIVE AUTONOMY OF THE CHILD AND ITS PARTICIPATION IN THE JUDICIAL PROCESS - Fernández Espinoza, William Homer (2017)
This research studies the issue of the progressive autonomy of children and adolescents  and the problems of their participation in the various processes in which they are involved, particularly related to their right of access to justice and the exercise of their right to be heard in the judicial sphere.